Obstacles and challenges identified by practitioners of non-formal science learning activities in Europe. Issue 3 (11th February 2022) - Christidou, Dimitra; Voulgari, Iro; Tisza, Gabriella; Norouzi, Behnaz; Kinnula, Marianne; Iivari, Netta; Papavlasopoulou, Sofia; Gollerizo, Adrián; Lozano González, Jose María; Konstantinidi Sofrona, Dafni
ABSTRACT: Despite the increasing demand for non-formal science learning activities, few studies report on practitioners' perspectives and experiences with designing and implementing such activities worldwide. This paper focuses on their challenges by drawing upon twenty-two interviews with practitioners involved in diverse science learning activities in various non-formal settings in seven European countries. By including diverse activities and settings, this study contributes to the existing knowledge base, addresses the aforementioned gap in the literature, and informs future practices. Our findings suggest that despite the existing and celebrated diversity, practitioners face similar challenges related to (a) the activities' organisation and management, (b) the competencies required to run such activities, and (c) the attitudes held by the parties involved in them. Direct interview quotes exemplify each theme, further pinpointing the interconnection of multiple factors that inform the organisation and implementation of non-formal science learning activities. The findings allowed for a deeper understanding of challenges reported in the literature and shed light on the challenges voiced by the practitioners including the multiple competencies required and the workload. We conclude with a discussion foregrounding the need to build a knowledge base of shared practices in the field of non-formal science learning.